1983
DOI: 10.1007/bf02013900
|View full text |Cite
|
Sign up to set email alerts
|

Synergy between the iron chelator deferoxamine and the antimicrobial agents gentamicin, chloramphenicol, cefalothin, cefotiam and cefsulodin

Abstract: Synergy between the iron chelator deferoxamine in the presence or absence of ascorbic acid and gentamicin, chloramphenicol, cephalothin, cefotiam or cefsulodin, used against Staphylococcus aureus, Staphylococcus epidermidis, Escherichia coli, Klebsiella pneumoniae, proteus mirabilis and species of Salmonella, Enterobacter, Pseudomonas and Providencia, was determined by measuring the effect of the drugs and combination of drugs on growth of the bacteria in an automated turbidimeter. The combination of drugs was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
27
0
1

Year Published

1991
1991
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 18 publications
2
27
0
1
Order By: Relevance
“…Gallium was found to be an effective competitive antagonist of the iron uptake, and the combined synergistic effects of gallium and gentamicin also supported a scenario where the high uptake of iron was critical for the bacterium to withstand the gentamicinmediated effects. In relation to previous data on the effects of iron chelation and the antibacterial effects of gentamicin, our findings support previously published studies that reported an additive or synergistic effect (16,17). and spleens of mice.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Gallium was found to be an effective competitive antagonist of the iron uptake, and the combined synergistic effects of gallium and gentamicin also supported a scenario where the high uptake of iron was critical for the bacterium to withstand the gentamicinmediated effects. In relation to previous data on the effects of iron chelation and the antibacterial effects of gentamicin, our findings support previously published studies that reported an additive or synergistic effect (16,17). and spleens of mice.…”
Section: Discussionsupporting
confidence: 92%
“…Numerous publications have implied that iron contributes to the bactericidal effect of aminoglycosides; however, the findings have to some extent been contradictory. Some studies implied that ferric iron promoted bacterial death and iron chelation mitigated the antibiotic effect (14,15), whereas other studies indicated that iron chelation acted in synergy with aminoglycosides against various Gram-negative and Gram-positive bacteria (16,17). We observed that the susceptibility of SCHU S4 to gentamicin in vitro was very significantly affected by both the intracellular iron depots and the extracellular availability of iron.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[4][5][6] Moreover, iron chelation therapy has been shown to work synergistically with antibiotics in the treatment of murine sepsis. 25,26 Several explanations for the differences with our findings in humans can be put forward. First of all, the majority of studies in which a beneficial effect of iron chelation therapy was found were performed in rodents or in vitro.…”
mentioning
confidence: 67%
“…They are lowmolecular-weight chelating agents that form stable complexes with iron [11,12]. There are many reports of the antimicrobial activity of chelating agents with different chemical structures [13][14][15][16][17][18][19]. Kojic acid (5-hydroxy-2-hydroxymethyl-pyran-4-one) and 3-hydroxypyranones, derivatives of it are examples of these compounds [13].…”
Section: Introductionmentioning
confidence: 99%